O consumo moderado de vinho tinto na prevenção de doenças cardiovasculares - Almeida, Camila Borella (Universidade do Vale do Rio dos Sinos, 2011)
Objective: To review the literature on the importance of moderate consumption of red wine in prevention heart disease. Methodology: The survey items available in the databases LILACS - BIREME, Medline, Pubmed, Scielo and in the last twelve years. Data synthesis: The results indicate that red wine and to a lesser extent, grape juice are rich in flavonoids, which improve endothelial function, leading to vasodilatation of the arteries and thereby reducing the development of cardiovascular disease. Conclusion: The authors have found that phenolic compounds from red wine only, reduce lipid peroxidation, chemical reactions mediated by free radicals, which can break down cellular structures and have consequences that oxidation of LDL (bad cholesterol), which is involved directly with the processes of atherosclerosis. The consumption of red wine in moderation can be beneficial to cardiovascular risk factors. However, the present evidence is insufficient to establish a recommendation for wine consumption in the general population, it is essential that longitudinal studies are performed with the red wine to obtain results more enlightening in relation to its benefits.
Keywords: Doenças cardiovasculares; Vinho tinto; Suco de uva; Cardiovascular disease; Red wine; Grape juice